3D Differential Equation Model for Patients' Choice of Hospital in China - Zhao, Xiaoxia; Jiang, Lihong; Zhao, Kaihong (Frontiers in Public Health, 2022)
The number of patients in a hospital is a direct indicator of patients’ choice of hospital, which is a complex process affected by many factors. Based on the national medical system and the preference of patients for high-grade hospitals in China, this study establishes a three-dimensional differential equation model for calculating the time variation of the number of visits to three grades of hospitals. We performed a qualitative analysis of the system and carried out subsequent numerical simulation to analyze the impact on the system when the rate of leapfrog treatment and the maximum capacity of doctors and treatments changed. The results show that the sustainability of China's three levels of hospitals mainly depends on the level of hospital development, and that the strength of comprehensive health improvement at specific levels is the key to increasing the service efficiency of medical resources.